2019
DOI: 10.1371/journal.pone.0223432
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the metabolic syndrome: Visceral and marrow adipose tissues impair bone quantity and quality in Cushing’s disease

Abstract: The present study was designed to evaluate the relationship between bone traits [bone mineral density (BMD) and trabecular bone score (TBS)] and the accumulation of fat in adipose tissues [abdominal subcutaneous (SAT), visceral (VAT), marrow (MAT) and intrahepatic lipids (IHL)], as well as insulin resistance, in subjects with Cushing’s disease (CD). The study included control (C = 27), paired (P = 16) and Cushing’s disease (CD = 10) groups, which underwent biochemical assessment, dual X-ray absorptiometry, TBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…It has been shown that hypercortisolism has a negative effect on bone due to decreased bone formation that it causes. Nevertheless, only a mild decline in BMD has been reported; whereas the TBS decline was more pronounced [ 87 , 88 ]. Moreover, TBS was lower in CD than in primary obesity patients, indicating the sensitivity of TBS to detect the variations along the hypercortisolism spectrum.…”
Section: Tbs In Endocrine-mediated Secondary Osteoporosismentioning
confidence: 99%
“…It has been shown that hypercortisolism has a negative effect on bone due to decreased bone formation that it causes. Nevertheless, only a mild decline in BMD has been reported; whereas the TBS decline was more pronounced [ 87 , 88 ]. Moreover, TBS was lower in CD than in primary obesity patients, indicating the sensitivity of TBS to detect the variations along the hypercortisolism spectrum.…”
Section: Tbs In Endocrine-mediated Secondary Osteoporosismentioning
confidence: 99%
“…In general, compared to control subjects, TBS was reported to be lower in patients with diabetes ( 42 , 57 59 ), primary hyperparathyroidism ( 60 64 ), acromegaly ( 65 68 ), anorexia nervosa ( 69 , 70 ), hypercortisolism ( 71 73 ), primary aldosteronism (especially in women) ( 74 ), with prolonged GC exposure ( 75 84 ), rheumatoid arthritis and rheumatic disease ( 85 87 ), aromatase inhibition ( 88 ), kidney transplant recipients ( 89 ), as well as in patients on hemodialysis ( 90 , 91 ). In differentiated thyroid carcinomas, TBS was found to be lower in patients receiving long-term suppressive doses of thyroid-stimulating hormone than in patients receiving shorter-term therapy ( 92 94 ).…”
Section: Tbs and Fracture Risk Prediction In Patients With Diabetes A...mentioning
confidence: 96%
“…The structural and functional skeletal damage is disabling and correlates with the patients' reported low quality of life [3,4]. According to data on bone density in endogenous hypercortisolism, patients with CS of adrenal, pituitary, or ectopic origin have marked osteopenia/osteoporosis [5,6].…”
Section: Introductionmentioning
confidence: 99%